The Efforts to Reduce The Risk of Learning Loss Through Limited Face-To-Face Learning - Aprilia Dian Sukmawati; Roni Harsoyo (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
The Covid-19 virus disease gap has caused a lot of problems, such as a significant decline in learning patterns ini educational institutions to the non-maximal implementation of online learning as a result, new problems aries, one of which is learning loss. This research was conducted to describe how the efforts of the MAN 1 Ngawi educational institution in minimizing the risk of learning loss that arises in distance learning through the application of limited face-to-face learning patterns. The method used by the author in this study is a qualitative concept in which the data obtained through the interview and observation process. This article tries to describe how the efforts of educational institutions at MAN 1 Ngawi to reduce the risk of learning loss that arise in distance learning through the application of the limited face-to-face learning (PTMT) pattern. The implementation of this PTMT gives great hope to the world of education in facing the curret pandemic, namely to improve the quality of the quality of educational institutions and restore student interest in learning which is slowly disappearing due to the distance learning gap through new habit patterns in implementing limited face-to-face learning.